COMMUNITY SOSIAL CHANGE DUE TO PLANTHOPPER PEST ATTACKS - Istiani, Shinta Ayu; Fitria, Nur Laili; Bramantha, Gerry (Jurnal Pertanian, 2019)
Pests pest very influential towards the production of rice in the hamlet of Mandiku Village Tempurejo District subdistrict of Jember Sidodadi. These pests invade rice caused by several factors, including: weather, seed varieties, trunks, and planting not outright. The factors are the root problems in the rice plant cultivation activities. The problems that arise should be minimised so that its influence is not prolonged and not harming farmers. Farmers in addressing the problem of pests must have the ability and knowledge in agricultural issues in particular concerning penanggulan pests. This research was conducted with the aim to find out the cause of social change, the impact of this pest attacks occur due to changes in society and the efforts of farmers in coping with pests pest in the village of Tempurejo Sub-district Sidodadi District Jember. The research method used is descriptive qualitative. Determination of informants in this study done by using purposive sampling. Data collection can be obtained using several ways namely observation, interview, Focus Group Discussion (FGD), and documentation.